Determinants of the Intention to Use Internet Banking - Hacini, Ishaq; Dahou, Khadra B.; Bendiabdellah, Abdeslam (Mediterranean Journal of Social Sciences, 2012)
The rapid development of internet and electronic business has stimulated the banking sector towards offering its services online.This paper examines the determinants of the individualâ€™s intention to use internet banking. While there has been considerableresearch on the technology acceptance model (TAM) that predicts whether individuals will accept to use information system, theresearch variables are developed based on an extended ( TAM ), by incorporating two additional variables â€œ perceived trust â€œ and â€œperceived self-efficacyâ€.The data was collected from 332 persons in Algeria through questionnaire. The hypotheses were tested usingmultiple linear regression to determine the effect of the variables on the intention to use internet banking. The results revealed that â€œperceived usefulness â€œ, perceived ease to use â€œ and â€œ perceived trust â€œ have positive significant effect, while â€œ perceived self-efficacy â€œhave no effect on the Algeriansâ€™ intention to use internet banking. They revealed also that â€œperceived trustâ€ has more influence on theintention to use internet banking than the other variables. A number of recommendations